Efektivitas Model Pembelajaran Problem Based Learning berbasis Socio-Scientific Issue ditinjau dari Kemampuan Berpikir Kritis Siswa pada Mata Pelajaran Ekonomi Fase E SMA Negeri 10 Muaro Jambi - Anggraeni, Fika; Liputo, Muhammad Arif; Dwijayanti, Novia Sri (Lembaga Yasin AlSys, 2025)
This study is motivated by the importance of developing students’ critical thinking skills in economics education, particularly in Phase E, as a response to complex social issues in society. The aim of the research is to examine the effectiveness of the Problem Based Learning (PBL) model based on Socio-Scientific Issues (SSI) in enhancing students’ critical thinking abilities in economics. A quantitative approach was employed using a quasi-experimental method with a nonequivalent group pretest-posttest design. The research sample consisted of 66 eleventh-grade students at SMA Negeri 10 Muaro Jambi, selected through purposive sampling, with 33 students each in the experimental and control classes. Data collection techniques included observation, testing, and documentation, while data analysis was conducted using an independent sample t-test on the posttest results. The test results show that the tₕᵢₜᵤₙg value of 7.322 is greater than the tₜₐbₑₗ value of 2.037 (α = 0.05; df = 64), with a significance level of 0.000 < 0.05, leading to the rejection of H₀ and acceptance of Hₐ. This indicates a significant difference in critical thinking skills between students taught using the PBL-SSI model and those taught with the expository method. The study concludes that the Problem Based Learning model based on Socio-Scientific Issues is effective in improving students’ critical thinking skills in economics. The findings imply that incorporating social issue-based approaches in instruction is recommended as a strategy for fostering students’ critical literacy toward real-world problems.